Mathematical modelling of radioactive dust rise during collapse of “Shelter” object building structures - Batiy, V.G.; Mikhailyuk, V.P.; Rubezhanskiy, Yu.I.; Rudko, V.M.; Sizov, A.A.; Fedorchenko, D.V. (Вопросы атомной науки и техники, 2004)
Model calculations of general dust quantity which is possible to raise during possible crashing of “Shelter” building structures are shown. Mechanism of particle “jump-up” i.e. raising of particles due to dusted surface oscillation is used during calculations. It is shown, that particles with diameter 20 µm are possible to overpass border sublayer and raise over ruins of the “Shelter” building.